Handbook of energy audits - Thumann, Albert. (Fairmont Press, 2013)
This best-selling handbook is the most comprehensive and practical reference available on energy auditing in buildings and industry. Topics include energy assessment and computer software which will guide you in planning and carrying out a thorough and accurate energy audit of any type of facility, including electrical, mechanical and building systems analysis. Clear, easy-to-follow instructions guide you through accounting procedures, rate of return and life cycle cost analysis. Also covered is information on understanding your utility bill and using that knowledge to trim your energy costs. Loaded with forms, checklists and handy working aids, book is required reading for anyone responsible for conducting or overseeing a facility energy audit.